ANALISIS DAMPAK PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP TINGKAT TURNOVER INTENTION - Chandra, Chintya (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
The author wrote this journal purpose is to determine the effect on turnover intention perceived organizational support driven by turnover problems in Indonesia which has yet to be resolved, and still be a scourge that is dangerous for any company. This issue can occur due to the level of Perceived Organizational Support that low in an enterprise. With the high level of awarenessof employees to this turnover rate then most likely intention in Indonesia Decrease more. With a declining turnover rate then the employee productivity to increase the company's value will increase. In the face of an MEA already opened and foreign companies had a great opening business in Indonesia. To narrow down the movement of the foreign company then local companies must increasingly strong and growing. Therefore it is necessary that high post so that employees feel more comfortable in the work environment and the level of Tunover Intention employees in Indonesia can be decreased. So with a low unemployment rate, the employee in Indonesia are not many who are unemployed and local companies getting stronger.